First Report in the Americas of S. enterica Var. Enteritidis Carrying blaNDM-1 in a Putatively New Sub-Lineage of IncC2 Plasmids - Nicolás F. Cordeiro; Romina Papa-Ezdra; Germán Traglia; Inés Bado; Virginia García-Fulgueiras; María N. Cortinas; Leticia Caiata; Mariana López-Vega; Ana Otero; Martín López; Patricia Hitateguy; Cristina Mogdasy; et al. (Antibiotics)
Background: Infections caused by carbapenem-resistant Enterobacterales have steadily multiplied over time, becoming a major threat to healthcare systems due to limited therapeutic options and high case-fatality rates. Case report: We studied a patient who, after being discharged from an ICU, developed salmonellosis caused by an antibiotic-susceptible S. enteritidis. After undergoing treatment with ciprofloxacin, the patient presented an episode of asymptomatic bacteriuria originated by a carbapenem and ciprofloxacin-resistant S. enteritidis. Results: Whole genome sequencing analysis revealed that both Salmonella isolates belonged to the same strain, and that isolate SEn_T2 acquired a plasmid carrying both blaNDM-1 and qnrA1 genes (pIncCSEn) which was previously present in the patient’s gut in at least one Enterobacter cloacae isolate. Additionally, pIncCSEN was identified as a putatively new sub-lineage of IncC2 plasmids which lacked the first copy of the methyltransferase gene dcm and the rhs gene. The resistance genes blaNDM-1 and qnrA1 were incorporated into a Tn21-derived transposon that included a complex class 1 integron whose genetic arrangement was: intI1- dfrA12- orfF- aadA2- qacEΔ1-sul1-ISCR1- trpF- ble- blaNDM-1 (in reverse direction)- ISAba125-ISCR1- qnrA- cmlA1- qacEΔ1-sul1. Conclusions: Antimicrobial persistence and co-selection of antibiotic resistance play an important role in the dissemination of antimicrobial resistance genes; in this regard, a joint effort involving the infection control team, effective antibiotic stewardship, and genomic surveillance could help mitigate the spread of these multidrug resistant microorganisms.